Etika dalam Pendidikan Politik (menghadapi bias dan propaganda) - Susilawati, Efi; Kurnia, Heri (CV. Kurnia Grup, 2024)
This study aims to analyze Ethical Issues in political education as one of the important aspects in shaping public awareness and participation in a Democratic system. However, ethical issues in political education are often overlooked. In this context, it is important to identify ethical values that should underline the practice of political education. The impact of Bias and Propaganda in political education can be very detrimental, not only to individuals, but also to society as a whole. Bias in education can create a false understanding of political issues and reduce an individual's ability to actively participate in the democratic process. This study uses a mixed approach, combining qualitative and quantitative methods. This mixed approach was chosen to provide a deeper understanding of the phenomenon of bias and propaganda in political education. By combining both methods, researcher can obtain more comprehensive and valid.